(untitled) (Information systems and technologies security, 2024)
The article proposes, shows and analyzes the main stages of implementing software for group assessment of a functional profile and determining or agreeing the level of guarantees for the correct implementation of functional security services in information security tools of information of telecommunication systems from unauthorized access in Ukraine based on theoretical studies previously conducted. The necessary regulatory documents on technical protection of information governing the procedure of evaluating and determining the level of guarantees of automated systems against unauthorized access in Ukraine are covered. The program was designed using the Data Flow Diagram, namely, a contextual diagram of the group definition process and a decomposed diagram of the process of group determination of the functional security profiles and the level of guarantees. More detailed flowcharts of software and algorithms are constructed. A prototype of the software is implemented; examples of work on each of the main blocks of work that were previously designed in the diagrams and flowcharts of the algorithms are given. Certain advantages and disadvantages of the developed software for group determination of the functional security profile and the level of guarantees are defined. The developed program allows to carry out group estimation and to compare the results sent to the server. This approach reduces the time spent by the security administrator to determine the security profiles and security levels of the information being processed against unauthorized access and to detect whether a specified functional profile coincides with a standard one (provided this match the user is provided with information about that standard functional profile) or determine another level of warranty. By conducting a group examination, the reliability of the obtained results increases.